2021
DOI: 10.18231/j.ijmmtd.2021.007
|View full text |Cite
|
Sign up to set email alerts
|

A study on clinical profile and laboratory parameters of dengue fever patients in Chennai, Tamil Nadu, India

Abstract: Dengue fever is the most important mosquito-borne viral disease, found to be endemic in tropical and subtropical countries. In recent decades, the incidence of dengue infection has increased around the world and has become a major public health concern. Materials and Methods: The prospective study was conducted during the period from July 2018 to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In our case, the patients had hemoptysis with other accompanying symptoms. In a recent study, hemoptysis was found to be 1.45–2.7 percent in the case of dengue fever, whereas in COVID‐19, it was about 13 percent 10,11 . COVID‐19 characteristics such as spike and nucleocapsid proteins activate the host's immune system, causing the virus to be eliminated.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, the patients had hemoptysis with other accompanying symptoms. In a recent study, hemoptysis was found to be 1.45–2.7 percent in the case of dengue fever, whereas in COVID‐19, it was about 13 percent 10,11 . COVID‐19 characteristics such as spike and nucleocapsid proteins activate the host's immune system, causing the virus to be eliminated.…”
Section: Discussionmentioning
confidence: 99%